First report of the genus Spicaticribra Johansen, Kociolek and Lowe in a Colombian reservoir and revision of the infrageneric taxa present in South America (2015)
ABSTRACT: The genus Spicaticribra Johansen, Kociolek, and Lowe is reported for the first time in Colombia, in surface sediment samples collected at Embalse La Fe. Materials were examined with light and scanning electron microscopies and their main morphologic and morphometric characters were compared to those of the remaining species of the genus. Based on these results we assigned them to Spicaticribra kingstonii and propose S. kodaikanaliana Kartrick and Kocioleck as a synonym. We conclude that the genus is represented in South America by only two species, S. patagonica Maidana restricted to the south region of the continent and S. kingstonii distributed across a broad latitudinal range